Case report: Acute liver failure during deferasirox therapy and the potential role of pharmacogenetics - García-Fariña, Belén; Rink, Lydia; Santarini, Virginia; Westkemper, Marco; Dohna-Schwake, Christian; Möhlendick, Birte (Frontiers in Pharmacology, 2024)
Background and aims: A number of case reports have documented the occurrence of acute hepatic and renal toxicity during treatment with deferasirox (DFX). The precise mechanisms underlying these adverse events remain unclear, with the time to toxicity varying considerably between patients—some experiencing it within weeks of treatment initiation, while others after several years. Recent studies have underscored the association of pharmacogenetic variants in genes responsible for the metabolism and clearance of DFX (ABCC2, ABCG2, and UGT1A1) in the development of toxicity. We present the case of an 8-year-old patient with beta thalassemia major who developed acute hepatic failure years after the initiation of DFX therapy. After ruling out the most likely causes, we performed a pharmacogenetic analysis, which suggested a possible link between the patient's genotype and the development of toxicity. Methods: Sanger sequencing was performed for the most extensively studied single nucleotide polymorphisms (SNPs) studied associated with changes in transporter/enzyme function: ABCC2 rs717620 (c.-24C>T), rs2273697 (c.1249G>A), rs8187710 (c.4544G>A), rs369192412 (g.99781071delG); ABCG2 rs2231142 (c.421C>A); UGT1A1 *6 rs4148323 (c.211G>A), *28 rs3064744 (g.233760235TA[8]), *36 rs3064744 (g.233760235TA[6]) and *37 rs3064744 (g.233760235TA[9]). Results: The patient is heterozygous for two ABCC2 variants, namely rs717620 (c.-24C>T) and rs2273697 (c.1249G>A). These variants have the potential to cause a reduction in transporter function, which could in turn result in decreased drug clearance and increased toxicity. Discussion: The precise mechanism by which toxicity developed in this case remains unclear and is likely multifactorial. However, it is probable that the presence of SNPs in the gene ABCC2 played a substantial role. Our findings align with those of previously published reports of remarkably similar cases, where patients also exhibited genetic variants in the gene ABCC2.